The KN-93 Molecule Inhibits Calcium/Calmodulin-Dependent Protein Kinase II (CaMKII) Activity by Binding to Ca2+/CaM. Issue 7 (29th March 2019) - Wong, Melanie H.; Samal, Alexandra B.; Lee, Mike; Vlach, Jiri; Novikov, Nikolai; Niedziela-Majka, Anita; Feng, Joy Y.; Koltun, Dmitry O.; Brendza, Katherine M.; Kwon, Hyock Joo; Schultz, Brian E.; Sakowicz, Roman; et al.
Abstract: Calcium/calmodulin-dependent protein kinase II (CaMKII) is a multifunctional serine/threonine protein kinase that transmits calcium signals in various cellular processes. CaMKII is activated by calcium-bound calmodulin (Ca 2+ /CaM) through a direct binding mechanism involving a regulatory C-terminal α-helix in CaMKII. The Ca 2+ /CaM binding triggers transphosphorylation of critical threonine residues proximal to the CaM-binding site leading to the autoactivated state of CaMKII. The demonstration of its critical roles in pathophysiological processes has elevated CaMKII to a key target in the management of numerous diseases. The molecule KN-93 is the most widely used inhibitor for studying the cellular and in vivo functions of CaMKII. It is widely believed that KN-93 binds directly to CaMKII, thus preventing kinase activation by competing with Ca 2+ /CaM. Herein, we employed surface plasmon resonance, NMR, and isothermal titration calorimetry to characterize this presumed interaction. Our results revealed that KN-93 binds directly to Ca 2+ /CaM and not to CaMKII. This binding would disrupt the ability of Ca 2+ /CaM to interact with CaMKII, effectively inhibiting CaMKII activation. Our findings also indicated that KN-93 can specifically compete with a CaMKIIδ-derived peptide for binding to Ca 2+ /CaM. As indicated by the surface plasmon resonance and isothermal titration calorimetry data, apparently at least two KN-93 molecules can bind to Ca 2+ /CaM. Our findings provide new insight into how in vitro and in vivo data obtained with KN-93 should be interpreted. They further suggest that other Ca 2+ /CaM-dependent, non-CaMKII activities should be considered in KN-93–based mechanism-of-action studies and drug discovery efforts. Graphical abstract: Unlabelled Image Highlights: CaMKII is activated by calcium-bound calmodulin (Ca 2+ /CaM). The molecule KN-93 is the most widely used inhibitor of CaMKII. We employed SPR, NMR, ITC, and enzymology to characterize the inhibition mechanism. We show that KN-93 binds directly to Ca 2+ /CaM and not to CaMKII. We offer new insight into how in vitro and in vivo KN-93 data should be interpreted.